Scrutinizing Public Expenditures : Assessing the Performance of Public Accounts Committees - Stapenhurst, Rick; Sahgal, Vinod; Woodley, William; Pelizzo, Riccardo (World Bank, Washington, DC, 2012)
In 2002, David McGee wrote a comprehensive report on two important elements in the system of public financial accountability, namely the office of the Auditor General and the parliamentary oversight committee commonly referred to as the Public Accounts Committee (PAC). The purpose of the present paper is to deepen McGee's analysis of PACs. In particular, the authors define PAC success and identify those factors that affect PAC peformance. They use data that were collected by the World Bank Institute in 2002, when a survey questionnaire was sent to 51 national and state/provincial parliaments in Commonwealth countries in Asia and Australasia, and Canada and the United Kingdom. The authors find that the institutional factors which most account for the success of the PACs are the focus on government's financial activity rather than its policies, the power to investigate all past and present government expenses, the power to follow up on government action in response to its recommendations, and its relationship with the Auditors General.